A comparison study between domestic and international rural tourist profile and travel expenditures in Semporna, Sabah - Chia, Kei Wei; Shuib, Ahmad; Ramachandran, Sridar; Mohammad Afandi, Syamsul Herman (Institut Kajian Dasar Pertanian dan Makanan, Universiti Putra Malaysia, 2015)
Tourist’s profile plays a vital role in tourism planning. This paper analyses the subject by comparing the tourist’s profile and travel expenditures between domestic and international tourists to Semporna, Sabah. This paper compares profile of tourists based on socio-demographic characteristics, trip related variables, and travel expenditures. Furthermore, travel expenditures are compared based on six different expenditure groups: accommodation, foods and beverages, transportation, diving services, others and total expenditure. This study uses face to face interview to obtain the results and the data was analysed using SPSS. The finding shows that the differences in socio-demographic characteristics, trip related variables, and travel expenditures between domestic and international tourists are noteworthy. Compare to domestic tourists, it was reported that international tourists prefer scuba diving and majority of them are first timer. They prefer to travel in a small group, with friends and spouse by bus and stayed at budget lodging. Also, international tourists stayed longer and know Semporna through words of mouth but they are less likely to purchase a package tour. Most of the international respondents are female, single, aged 19 to 40, had higher education background and work as private employees or self-employed. The average income for international tourists is RM7535 and they spent average RM1927. Finally, the main conclusions and implications for tourism marketing are discussed following by the recommendations.